Attitudes Toward the Copper IUD in Sweden: A Survey Study - Wemrell, Maria; Gunnarsson, Lena (Frontiers in Global Women's Health, 2022)
Background: While the efficacy and safety of the contraceptive copper intrauterine device (IUD) have been affirmed, alongside its importance for the prevention of unintended pregnancies, some studies have pointed to negative attitudes toward the device. In recent years, social media communication about it has included claims about systemic side effects, unsubstantiated by medical authorities. Research from the Swedish context is sparse. This study investigates attitudes toward the copper IUD, and any correlations between negative attitudes toward or experiences of the device and (1) sociodemographic characteristics, (2) the evaluation of the reliability of different sources of information, and (3) trust in health-care and other societal institutions. Methods: A survey was distributed online to adult women in Sweden (n=2000). Aside from descriptive statistics, associations between negative attitudes toward or experiences of the copper IUD and sociodemographic other variables were calculated using logistic regressions and expressed as odds ratios (ORs) with 95% confidence intervals (95% CIs). Open survey responses (n=650) were analyzed thematically. Results: While many reported positive attitudes toward and experiences of the IUD, 34.7% of all respondents reported negative attitudes and 45.4% of users reported negative experiences. Negative attitudes were strongly correlated with negative experiences. Negative attitudes and experiences were associated with low income, but no conclusive associations were identified with other socioeconomic variables. Negative attitudes and experiences were associated with lower levels of confidence in and satisfaction with health-care, and lower self-assessed access to and ability to assess the origin and reliability of information about the IUD. In open responses, negative comments were prevalent and included references to both common and unestablished perceived side-effects. Respondents pointed to problematic aspects of information and knowledge about the copper IUD, and called for improved health-care communication and updated research. Conclusion: Health-care provider communication about the copper IUD should promote reproductive autonomy and trust by providing clear information about potential side effects and being open to respectfully discuss women’s experiences and concerns. Further research on copper IUD dissatisfaction, and ways in which health professionals do and may best respond to it, is needed.